2014
DOI: 10.1002/etc.2719
|View full text |Cite
|
Sign up to set email alerts
|

Variation in riparian consumer diet composition and differential bioaccumulation by prey influence the risk of exposure to elements from a recently remediated fly ash spill

Abstract: Emerging aquatic insects play a key role in transporting aquatic nutrients and contaminants to riparian consumers. However, little is known about how within- and between-year variation in the diet or patterns of element bioaccumulation in emerging insect taxa may influence the risk of exposure to wildlife. During 2 breeding seasons, the composition of the diet of tree swallows (Tachycineta bicolor) was examined at several colonies that were exposed to element contamination from a remediated coal fly ash spill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Dietary studies of nestling and adult tree swallows (Tachycineta bicolor) around the spill site suggest some trophic transfer through insects that have an aquatic stage (mostly chironomids, but mayflies also were found in the diet). However, the concentrations of contaminants were not associated with any lethal or sublethal physiological effects [57,58]. Downstream of the ash spill redear sunfish (Lepomis microlophus), a species likely to have a diet predominantly of aquatic organisms, were found to have elevated levels of Se [59] and evidence of possible sublethal physiological changes [60].…”
Section: Ecological Relevance Of Contaminant Exposuresmentioning
confidence: 99%
“…Dietary studies of nestling and adult tree swallows (Tachycineta bicolor) around the spill site suggest some trophic transfer through insects that have an aquatic stage (mostly chironomids, but mayflies also were found in the diet). However, the concentrations of contaminants were not associated with any lethal or sublethal physiological effects [57,58]. Downstream of the ash spill redear sunfish (Lepomis microlophus), a species likely to have a diet predominantly of aquatic organisms, were found to have elevated levels of Se [59] and evidence of possible sublethal physiological changes [60].…”
Section: Ecological Relevance Of Contaminant Exposuresmentioning
confidence: 99%
“…(2016 , 2018 ) provides strong evidence that aquatic insects provide critical nutritional benefits to aerial insectivorous birds; accordingly, other studies of aerial insectivore diets have demonstrated a reliance on aquatic insect subsidies (e.g. Beck et al , 2014 ; Michelson et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adult aquatic insects, which form a significant portion of the diet of some terrestrial organisms [7], inevitably emerge from contaminated sediments and transfer body burden to the terrestrial environment either directly as prey items to insectivores, or indirectly through the detritus food chain [8]. A number of studies [9][10] have shown that both immature and emerging insects play a crucial role in determining metal contaminants in the environment. Currie et al [11] collected emerging insects (Diptera, Odonata, Ephemeroptera, and Trichoptera) from lake water in order to quantitatively estimate the export of cadmium by aquatic insects from a natural system having elevated cadmium concentrations in the water and sediment.…”
Section: Introductionmentioning
confidence: 99%